Exploring host‐associated differentiation in the North American native cranberry fruitworm, Acrobasis vaccinii, from blueberries and cranberries. Issue 2 (27th December 2013) - Medina, R.F.; Szendrei, Z.; Harrison, K.; Isaacs, R.; Averill, A.; Malo, E.A.; Rodriguez‐Saona, C.
Abstract The factors explaining host‐associated differentiation (HAD) have not yet been fully characterized, especially in agricultural systems. It is thought that certain characteristics within a system may increase the probability for HAD to occur. These characteristics include relatively long‐standing evolutionary relationships between insects and their host plants, endophagy, and allochrony in host‐plant phenologies. We assessed the status of these characteristics as well as the presence of HAD in the cranberry fruitworm, Acrobasis vaccinii Riley (Lepidoptera: Pyralidae), a pest associated with blueberry and cranberry in eastern North America. We reveal the occurrence of two distinct populations of A. vaccinii that are allochronically isolated by the phenological stage of their respective host plants (cranberries or blueberries). Laboratory‐reared A. vaccinii adults collected from blueberries emerge at least 1 week earlier than adults from cranberries and the antennal sensitivity of adults to host‐plant volatiles differs between A. vaccinii collected from blueberry and cranberry. Despite finding characteristics indicative of HAD, we did not detect a genetic signature of HAD in A. vaccinii. These findings suggest that HAD may occur through behavioral and phenological mechanisms before there is sufficient genetic variation to be detected.